2021
DOI: 10.1002/chem.202002394
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Strategy for Cofacial Porphyrin‐Based Homo‐ and Heterobimetallic Complexes

Abstract: We present a straightforward and generally applicable synthesis route for cofacially linked homo‐ and heterobimetallic porphyrin complexes. The protocol allows the synthesis of unsymmetrical aryl‐based meso‐meso as well as β‐meso‐linked porphyrins. Our method significantly increases the overall yield for the published compound known as o‐phenylene‐bisporphyrin (OBBP) by a factor of 6.8. Besides the synthesis of 16 novel homobimetallic complexes containing MnIII, FeIII, NiII, CuII, ZnII, and PdII, we achieved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Next, the as‐synthesised free‐base ligand with the trans/cis ratio of 98 : 2 was triply metallated with six different transition metals (Scheme 5), and the resulting metal complexes, bearing the same trans/cis ratio were systematically analysed with UV‐Vis, IR‐spectroscopy, MS and IMS. For the metal coordination, we observed that reaction times needed to be only slightly extended relative to our previous dimer work to obtain complete three‐fold complexation [17] . Exceptionally this does not hold for the 3Ni‐OBTP 13 complex since we observed degradation while stirring in DMF at 100 °C.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…Next, the as‐synthesised free‐base ligand with the trans/cis ratio of 98 : 2 was triply metallated with six different transition metals (Scheme 5), and the resulting metal complexes, bearing the same trans/cis ratio were systematically analysed with UV‐Vis, IR‐spectroscopy, MS and IMS. For the metal coordination, we observed that reaction times needed to be only slightly extended relative to our previous dimer work to obtain complete three‐fold complexation [17] . Exceptionally this does not hold for the 3Ni‐OBTP 13 complex since we observed degradation while stirring in DMF at 100 °C.…”
Section: Resultsmentioning
confidence: 64%
“…We have developed a facile synthetic route towards the novel o ‐phenylene‐trisporphyrin (free base OBTP, 6H‐OBTP) 3 as a cofacial ligand system (Scheme 1) using pyrrole and benzaldehyde as starting materials. As previously reported by us for bisporphyrins, we have used the well‐established condensation of two pyrroles 1 with paraformaldehyde to yield dipyrromethane 4 in 65 % yield to begin the seven‐step reaction procedure [17,18] . 4 can be used to build up trans‐substituted porphyrin cores like 5,15‐diphenylporphyrin ( 5 ) if benzaldehyde is employed as the corresponding aldehyde [19] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11] Tuning multinuclear metal complexes, among various contributing factors based on the nature of the metal type, oxidation state, and coordination capabilities, M-to-M distance modulation has been a promising approach for identifying and optimizing structureproperty relationship from the perspective of cooperative effects. [12] Ligand design is of utmost relevance in investigating structure-property relationships and stands at the center from the application perspectives of metalloarenes. [13] Structural features of the bridging ligand such as flexibility or rigidity, steric, electronic effects, spatial orientation, and systematic variation of M-to-M distances to comprise novel functionalities are crucial contributing factors.…”
Section: Introductionmentioning
confidence: 99%